Ted K: Unabomber. [videorecording (DVD)] - Copley, Sharlto, 1973-; Powell, Drew, 1976-; Pyle, Wayne (Decal, 2022)
An exploration of Ted Kaczynksi's life in Lincoln, Montana in the years leading up to his arrest as The Unabomber.